Transplanting the leafy liverwort Herbertus hutchinsiae: a suitable conservation tool to maintain oceanic-montane liverwort-rich heath?. (3rd March 2016) - Flagmeier, Maren; Hollingsworth, Peter M.; Genney, David R.; Long, David G.; Muñoz, Jesús; Moreno-Jiménez, Eduardo; Woodin, Sarah J.
Abstract : Background : Translocating plants for conservation purposes can be a useful tool to enhance existing populations, restore lost populations or create new ones, but has rarely been done for bryophytes, especially liverworts. Aims : Here, the leafy liverwort Herbertus hutchinsiae, a representative species of oceanic-montane liverwort-rich heath, was translocated to unoccupied habitat within its current range, to establish whether its restricted distribution is due to habitat or dispersal limitation. Methods : Feasibility of establishing new populations outside the current distribution range was assessed, to test the suitability of the species for assisted colonisation. Furthermore, transplants were grown at degraded sites where the species had declined to assess potential for restoration. Results : Although maximal growth rates occurred within-range, transplants grew at all sites, indicating that the species could be dispersal limited; a conclusion supported by distribution modelling. Conclusions : Assisted colonisation is thus an option for this species to overcome dispersal limitation and to track future climate space. Reinforcement of populations at degraded sites is only recommended if the pressure causing the degradation has been removed. These findings provide an evidence base for practical conservation management.